Development of a Systematic Review of Public Health Interventions to Prevent Children Drowning - Crawford, Gemma; Leavy, Justine; Portsmouth, Linda; Jancey, Jonine; Leaversuch, Francene; Nimmo, L.; Reid-Dornbusch, Lauren; Hills, Emma (Scientific Research Publishing, 2014)
Drowning is the leading cause of death from unintended injury in children globally. Drowning is preventable, and mechanisms exist which can reduce its impact, however the peer-reviewed literature to guide public health interventions is lacking. This paper describes a protocol for a review of drowning prevention interventions for children. Electronic searching will identify relevant peer-reviewed literature describing interventions to prevent child drowning worldwide. Outcome measures will include: drowning rates, water safety behaviour change, knowledge and/or attitude change, water safety policy and legislation, changes to environment and water safety skills. Quality appraisal and data extraction will be independently completed by two researchers using standardised forms recording descriptive and outcome data for each included article. Data analysis and presentation of results will occur after data have been extracted. This review will map the types of interventions being implemented to prevent drowning amongst children and identify gaps within the literature.